Parameter optimization of toroidal tuned liquid column dampers for suppressing multi-directional harmonic vibration of structures. Issue 1 (2nd January 2022) - Ding, Hao; Wang, Jin-Ting; Lu, Li-Qiao; Pan, Jian-Wen
Abstract : In this article, optimization of the toroidal tuned liquid column damper (TTLCD) for suppressing harmonic vibration is investigated. First, a closed-form solution for the TTLCD–structure system is derived. Based on the solution, optimization is carried out and some design tables listing the optimum parameters are obtained. Secondly, a parametric investigation of key parameters that affect the damping properties of the TTLCD–structure system is performed to reveal how to produce optimal damping effects. Finally, a design example of the TTLCD is illustrated. A conventional TLCD is also designed based on the same controlled structure for comparison. The results reveal that the TTLCD can maintain the equivalent damping ratio of the system at a high level in arbitrary directions, while the TLCD has a high damping ratio in its main control direction but falls significantly in the direction perpendicular to its main control direction.